2019
DOI: 10.1186/s41239-019-0165-y
|View full text |Cite
|
Sign up to set email alerts
|

Using scaffold innovation-thinking frameworks to integrate food science and technology into the transdisciplinary engineering design classroom

Abstract: Technology and innovation are essential for students to not only learn and understand the technical skills, but also identify a problem, discover a solution, and communicate the value proposition. In this study, innovation-thinking frameworks were integrated into undergraduate transdisciplinary engineering and technology classrooms with a topic of food science and technology, exploring design within the area of new product development. The qualitative analysis, conducted using NVivo, indicated that the food sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In this respect, the contents and delivery options of FE material have to match the learning outcomes expected by audiences with different backgrounds and interests. In academia, the quantity and scope of some FE-related programs have expanded to accomodate an interdisciplinary vision that brings in aspects of innovation, sustainability, consumer sciences, and gastronomy [40,41,42]. Besides, employers in the food and restaurant sectors are demanding a formation in "soft skills" that encourages communication abilities, critical thinking, problem-solving capacities, and working in groups [36,23].…”
Section: Food Engineering Programs Around the Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the contents and delivery options of FE material have to match the learning outcomes expected by audiences with different backgrounds and interests. In academia, the quantity and scope of some FE-related programs have expanded to accomodate an interdisciplinary vision that brings in aspects of innovation, sustainability, consumer sciences, and gastronomy [40,41,42]. Besides, employers in the food and restaurant sectors are demanding a formation in "soft skills" that encourages communication abilities, critical thinking, problem-solving capacities, and working in groups [36,23].…”
Section: Food Engineering Programs Around the Worldmentioning
confidence: 99%
“…Although most students valued the experience of the term project, some requested clearer instructions of the expectations. The complaint is usual in food science students exposed for the first time to this type of assignments and was improved in 2020 with a detailed rubric for the term project [40,98]. A few comments pointed out that lectures were sometimes redundant, a matter that is a common criticism for flipped class courses [93].…”
Section: Evaluation Of the Coursementioning
confidence: 99%
“…However, society is identifying new challenges in terms of the healthiness and sustainability of the different diets (Dernini et al, 2017;Serra-Majem & Medina, 2015) as whole food systems (the recently published and controversial article by Willett et al, 2019, should be a good example).On the other hand, the food field has developed and demands its own methodologies, increasingly seeking interdisciplinarity (de Garine, 2004;McClancy & Macbeth, 2004). As Bosman and Eom (2019) points out in their article published in this collection, the benefit of exploring and designing around the theme of food science and technology exists in the transdisciplinary nature of food which covers the gamut of business viability and economic analysis, customer desirability and consumer behaviours, and technical feasibility and prototyping.…”
Section: Introductionmentioning
confidence: 99%
“…On lights… Higher education, and particularly postgraduate programmes in Food, Food Science, Nutrition and Health, take a multidisciplinary approach, combining subjects such as nutrition, food science, psychology and, more and more frequently, social and cultural perspectives. Following Bosman and Eom's (2019) review of literature in this collection, different research on food postgraduate virtual programmes showed important teaching-related benefits that have contributed in a significant way to the success of these programmes. In this regard, they show how authors like Cohen (2010) points out after his evaluation of a cross-disciplinary undergraduate course that integrates design and liberal arts intending to improve the sustainability of the school's food system, that the course was effective and helpful in learning about sustainability and urban systems through research, problem-solving, and communication.…”
Section: Introductionmentioning
confidence: 99%
“…However, the STEAM approach is primarily applied in preliminary and secondary education [7] [8], and has scarcely been documented in tertiary education. Some practices that are interdisciplinary or even more transdisciplinary in nature, and follow the STEAM approach are referred to as Innovation-thinking frameworks [9]. However, the use of these frameworks in engineering technology programs is not well-documented in literature.…”
Section: Current Approaches To the Problem And Gapsmentioning
confidence: 99%